SCRATCH SOFTWARE AND ITS OPPORTUNITIES (Conference Zone, 2022)
Scratch is a block visual programming language and website designed primarily for children ages 8-16 to help them learn code. Site users can create projects on the Internet using a block-like interface. Scratch is taught and used in after-school centers, schools and colleges, as well as other public education institutions